Evaluasi Geometri Jalan Tambang Di PT Vitrama Properti Desa Air Mesu Kabupaten Bangka Tengah - Selvira Oktaviani; Janiar Pitulima; Haslen Oktarianty (MINERAL, 2021)
PT Vitrama Properti is a company engaged in mining sector that utilizes natural resources of granite. The condition of mine road at PT Vitrama Properti is not good, causing the lack of transportation productivity in the transportation process. This study aims to evaluate the geometry of the mine road. The method is terrestrial method. Data that obtained are data on straight road width, road width at bends, height differences and bend radius to evaluated with AASHTO. The smallest of road width is 4.67 m, the road width on the smallest bend is 5.8 m, the smallest height difference value is 0.9 m and the smallest radius of bend is 7.695 m. The evaluation results are the width of the haul road on a straight single lane minimum is 6.6 m, the width of the haul road on a straight two-lane minimum is 11.55 m, the width of haul road in two lines minimum bend is 16.485 m, the maximum slope of road is 10%, the superelevation is 4%, and the cross slope is 33 cm.